KAJIAN HADIST TENTANG URGENSI KEMAMPUAN DALAM MENIKAH : Analisis Permasalahan Pernikahan Usia Dini di Indonesia - Siswanto, Siswanto; A'yun, Vina Qorrotu; Permana, Dede (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2022)
Underage marriages that have happened in Indonesia from year to year have caused many problems not only in terms of social aspect, but also in the health. Even though it has clearly violated the laws and regulations that have been set, but in its implementation, it still requires moral and religious legitimacy. The assumption that Islam allows underage marriage through a narrow understanding of hadith needs further study and research, so that Islamic guidances can be in harmony and suitable with mutually agreed laws and regulations. Marriage as a great agreement (mītsāq ghalīzh) requires good preparation in the form of optimal abilities as the prophet's suggestion that contained in the hadith narrated by Ibnu Mas'ud.